Scientific and educational publications of People’s Poland in the light of censorship reviews of the 1950s - Wiśniewska-Grabarczyk, Anna (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
In the paper I analyze selected censorship strategies towards scientific and educational publications evaluated by the Polish Censorship Office in 1950s. These strategies involve: evaluation of literature cited in the papers, elimination of confidential and problematic informations, resignation from scientific evaluation for the purpose of ideology. My analysis shows that censorship reviews were just one of the links in the chain of the publication process and that the aim of most of them was only the evaluation of ideological engagement. Scientific publications were risky for censors as they could humiliate them because they showed their „competence barriers”. Because of this they show real aims of censorship and the shallowness of the factual level of evaluation better than then typical censorship of literature.